Reflective Teaching Practice as a Gateway to Professional Development: The Case of EFL Teachers of The Dahra Region in Relizane - BEKHEIRA, Fatima Zahraa (My University, 2024)
The complexity of the 21st-century educational system demands teachers’ effective competencies and skills namely their higher-level thinking, specifically, their reflective thinking. By adopting this skill, teachers can critically think about their teaching practices and make future changes accordingly. Consequently, they continue to improve their teaching performance, positively increase their students’ learning, and especially promote their professional development. Therefore, the current research investigated reflective teaching practice as a gateway to professional development. This study emphasizes the importance of reflective teaching practice in improving teachers’ PD. It was mainly conducted to unveil whether high school EFL teachers of the Dahra region are reflective practitioners or not. Under this main question, the researcher wanted to investigate the reasons behind EFL teachers’ lack of reflection and how it affects their teaching performance and students’ learning. Moreover, the study attempted to explore whether EFL high school teachers want to improve professionally or not. Hence, it is hypothesized that high school EFL teachers are not reflecting because they may not be aware of the reflective teaching practice’s importance in their teaching. Further, they do not reflect on their teaching practices because they may face challenges. Additionally, it proposed that lack of reflection has a negative impact on EFL teachers’ teaching performance and their students’ learning. In addition, the study has been carried out under a descriptive-analytical method. To collect the data, a semi-structured questionnaire was submitted to 20 high school EFL teachers and a semi-structured interview was conducted with 05 teachers from the same participants to test the research hypotheses. The research findings revealed that most of the informants do not engage in the process of RTP as they are not aware of its importance. Hence, lack of RTP negatively affects their teaching performance and students’ learning. Moreover, the research participants desire to improve professionally. However, they do not take action to attain this goal. Accordingly, the current study revealed that RTP is a great process for increasing EFL teachers’ PD since it helped the other minority of participants to improve their teaching performance and students’ learning. Therefore, based on the obtained results, the previously stated hypotheses were confirmed.
Keywords: EFL teachers; professional development; reflection; reflective practice